A Review on Criminological Approaches to Religious Terrorism - Farhad Shahideh; Jaʿfar Kousha (مطالعات فقه اسلامی و مبانی حقوق, 2023)
There is a complicated relationship between religion and terrorist crime. On the one hand, the teachings of Islam seek to create peace and security in society by rejecting any violent behavior, and on the other hand, a misunderstanding of religion can lead to religious terrorism. The teachings and doctrines of Islam, on the one hand, seek to create peace and security in society by rejecting any violent behavior and on the other hand, misunderstanding of religion can lead to religious terrorism. One of the issues that have not been given much attention in criminology is the relationship between ideology and crime. However, the ideology causes the most serious and heinous crimes to be committed, including terrorism. Although different ideologies may cause crimes, religious ideology is one of the most important forms in which people commit crimes by adhering to religious teachings. The perpetrators in religious terrorism such as the members of the Islamic State terrorist group (ISIS) insist on their religious thoughts without interaction and dialogue and they consider themselves superior by an incorrect understanding of the values and ideas of that religion and provide the basis for violence and prejudice. The religious ideology is discussed by descriptive and analytical method in the light of religious criminology in this context. Terrorist perpetrators who eliminate the internal barriers of committing crimes by neutralization techniques are influenced by negative religious feelings according to theoretical criminology findings and thoughts and commit terrorist behavior without fear of punishment and lack of understanding of obscene act. It is tried to explain by a model of applied criminology based on this and using religious teachings, religious and moral prevention and deradicalization of terrorist perpetrators.